Implementation of Empathetic Pedagogy in Early Childhood Education: A Systematic Review of the Literature - Rini Herminastiti; Ambar Pawitri (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Empathetic pedagogy has emerged as a pivotal framework in strengthening the socio-emotional resilience of young children, especially in the post-pandemic digital era. This study aims to systematically conceptualize the operationalization, instructional strategies, and multidimensional impacts of empathetic pedagogy within Early Childhood Education (ECE) ecosystems through a qualitative descriptive-analytical literature review. Data were systematically collected from Google Scholar, Sinta, and Scopus (2016–2026), and analyzed using thematic content analysis techniques. The synthesis confirms that empathetic pedagogy operates through a tripartite architecture: cognitive empathy (perspective-taking), affective empathy (emotional resonance), and compassionate action (regulatory response). Three effective micro-instructional strategies were identified: teacher modeling, restructuring the morning circle into listening spaces, and digital-reflective bibliotherapy. Consistent implementation of these strategies has been shown to improve emotional regulation, strengthen prosocial behavior, and foster an inclusive classroom climate based on secure attachment. This study recommends the reformulation of curricula and teacher training grounded in empathy, as well as the integration of digital innovations in ECE learning practices. The findings provide conceptual and practical foundations for developing early childhood education that is more humanistic and responsive to children’s emotional needs.